Is it time for transition from the subject-based to the integrated preclinical medical curriculum? - Kapitonova, Marina; Gupalo, Sergey P.; Dydykin, Sergey Sergeevich; Vasil’ev, Yury L.; Mandrikov, Viktor B.; Klauchek, Sergey V.; Fedorova, Olga V. (RusOMJ, 2020)
In the 60s of the last century, a number of new universities in the world began to apply an integrated program of medical education, the cornerstone of which was problem-oriented education. Thus, the Flexner model of higher education adopted by that time in most countries of the world, with its characteristic segregation of teaching of the theoretical and clinical disciplines, which had ceased to satisfy the needs of modern healthcare, was gradually replaced by a new system that put the student in the center of the educational process and opened the way to active methods of teaching being focused on the end result – training of graduates whose qualifications most fully satisfy the needs of society. Over the half-century history of its existence, this system has been adopted by most medical universities in different countries of the world, in many of which it has undergone significant modifications in accordance with the needs of national educational standards. Many medical universities in Russia and other countries of the former Soviet Union showed interest in this system, some of the medical faculties of our country accepted certain elements of it. However, up to date no integrated preclinical medical education program has been applied in any of the Russian universities. Hereby we are undertaking an attempt to analyze the reasons and assess the possible perspectives for the transition of medical universities in Russia to teaching of fundamental and biomedical disciplines using the integrated curriculum.